Experimental investigation on turbulent heat transfer characteristics of molten salt in a shell-and-tube heat exchanger. (5th September 2016) - He, Ya-Ling; Zheng, Zhang-Jing; Du, Bao-Cun; Wang, Kun; Qiu, Yu
Highlights: A novel large-scale experimental platform for testing the molten salt is built. Turbulent heat transfer performance of molten salt in tube bundle was investigated. Similarity of heat transfer performance between molten salt and water is discussed. Empirical correlation of molten salt in shell-and-tube heat exchanger is obtained. Abstract: A new experimental platform was built to measure the flow and heat transfer characteristics of molten salt in some large-scale heat exchangers. Based on this experimental platform, the turbulent heat transfer characteristics of a shell-and-tube heat exchanger designed for molten salt were investigated. The tube-side and shell-side Reynolds number vary from 10, 000 to 91, 000, and from 11, 000 to 27, 000, respectively. The heat transfer characteristics of water in the same heat exchanger were also measured to confirm the accuracy and usable range of experimental results. The results showed that the deviation of tested convective heat transfer coefficients between molten salt and water is just 14.1% which is comparable to the experimental uncertainty of 12.8%. Therefore, in view of decreasing the difficulty and cost of experiment, water is suggested to replace molten salt for measuring the heat transfer characteristics of molten salt heat exchanger. In addition, some empirical correlations for heat transfer characteristics in both sides of heat exchanger were obtained. The tube-side correlations agree well with the typical Dittus-Boelter correlation with an allowable difference of 10%. The difference between shell-side correlation and the Dittus-Boelter correlation is also less than 20% when the proper hydraulic diameter is selected as the characteristic dimension.